NEW METHOD FOR COMPLETING SORTING FROM COTTON FIBER - Yusupalieva U.N.; N.A. Sadikova (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
This article discusses a new methodology for compiling sortings for the production of cotton yarn of various assortments and purposes. The disadvantages and inappropriateness of using existing standard sortings in spinning production in cotton-textile clusters are analyzed. The proposed new technique provides the necessary planning for mixing cotton fiber with a limited number of mixture components. The recommended technique also ensures the necessary increased requirements, especially the color shades of the produced yarn, making maximum use of the fiber indicators determined by the HVI system